Implementasi Model Guided Discovery untuk Meningkatkan Keterampilan Proses Sains Siswa Kelas XI IPA SMA Negeri 10 Rejang Lebong: Implementasi Model Guided Discovery untuk Meningkatkan Keterampilan Proses Sains Siswa Kelas XI IPA SMA Negeri 10 Rejang Lebong - Fitra Erlinda (GHAITSA : Islamic Education Journal, 2020)
Chemistry learning process carried out at Rejang Lebong 10 High School which has not yet taken a whole scientific approach so it tends to focus on providing material directly without going through scientific processes such as experimental activities. The purpose f this research is to improve the science process skills of students of class XI IPA 1 at SMA Negeri 10 Rejang Lebong. This research is a class action research (Classroom Action Research). The research subjects were all students of class XI IPA-1 SMA 10 Rejang Lebong in the 2019/2020 school year consisting of 12 men and 18 women. The instrument used was a knowledge assessment test to evaluate the process skills test. The study was conducted in two cycles with an average value of students in the first cycle of 75.76 and the second cycle of 89.73. an increase of 13.97 for the science process skills test concluded that the implementation of guided discovery models in the concept of Reaction Rate can improve the science process skills of students of class XI IPA 1 SMA 10 Rejang Lebong for observing indicators, asking questions, making hypotheses, conducting experiments and communicating